Developing a Risk Management Framework in Construction Project Based on Agile Management Approach - Mohammed Neamah Ahmed; Sawsan Rasheed Mohammed (Salehan Institute of Higher Education, 2019)
Construction projects in nature, carry a lot of risks, and unpredictable conditions. Thus, flexible management is required for the purpose of efficient responding to the various changes appear during their implementation. As an attempt to deal with risk in the construction project, this research aims at proposing a risk management framework in construction projects that built based on Agile management concept, which is a sequence of procedure deals with the project’ primary vision to its final delivery. The risk management framework will trace alignment and discover a contact between Agile and traditional project management concepts and find contact points among two of the more used Agile frameworks (Scrum) and one of the more confirmed project management framework (PMBOK®) processes. This will result in a recognition of comparable areas between Scrum and PMBOK® processes. The goal of the framework is to assist the project managers to adapt a more flexible approach to managing and implementing the construction project. The results proved that Agile management process from the create prioritized project backlog, sprint planning, sprint review, to sprint retrospective procedures and less time of the cycle, eliminate or mitigate many risks that lead to project challenges and failure.